1998
DOI: 10.1002/etc.5620171215
|View full text |Cite
|
Sign up to set email alerts
|

Mercury‐induced micronuclei in skin fibroblasts of beluga whales

Abstract: Abstract-Beluga whales (Delphinapterus leucas) inhabiting the St. Lawrence estuary are highly contaminated with environmental pollutants and have a high incidence of cancer. Environmental contaminants may be partly responsible for the high incidence of cancer observed in this population. DNA damage plays an important role in the development of cancer. The micronuclei assay was used to test the genotoxic potential of mercury compounds in skin fibroblasts of an Arctic beluga whale. Both mercuric chloride (Hg) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…64 Mercury methyl hemoglobin is another suspected carcinogen in St. Lawrence belugas (D. leucas) and has been documented to produce multimicronucleation in fibroblasts because of genotoxic effects. 33 Endocrine disruption by PCBs is well documented. A role in the development of thyroid neoplasia may result from a decrease in plasma concentrations of thyroid hormones followed by a compensatory increase in thyroid stimulating hormone (TSH) secretion by the hypophysis;.…”
Section: Chemical Carcinogensmentioning
confidence: 98%
See 2 more Smart Citations
“…64 Mercury methyl hemoglobin is another suspected carcinogen in St. Lawrence belugas (D. leucas) and has been documented to produce multimicronucleation in fibroblasts because of genotoxic effects. 33 Endocrine disruption by PCBs is well documented. A role in the development of thyroid neoplasia may result from a decrease in plasma concentrations of thyroid hormones followed by a compensatory increase in thyroid stimulating hormone (TSH) secretion by the hypophysis;.…”
Section: Chemical Carcinogensmentioning
confidence: 98%
“…40 In addition, organochlorine compounds and mercury induced micronuclei in beluga skin fibroblasts. 33,34 Biomarkers of DNA damage in marine mammals include micronuclei, sister chromatid exchange, and chromosome aberration. 33,35 DDT, toxaphene, and chlordane compounds were the major pesticide derivatives found in the St. Lawrence beluga whales (D. leucas), and all of these compounds had direct genotoxicity in beluga whale fibroblasts in vitro.…”
Section: Chemical Carcinogensmentioning
confidence: 99%
See 1 more Smart Citation
“…The direct effects of elevated MeHg on marine biota can include impacts on neurologic end points and memory, locomotion, and cognition, as well as changes in brain neurochemical receptor density (Basu et al 2005; Scheuhammer et al 2008). Adverse effects may further manifest as immunosuppression, which may make individuals more susceptible to disease, as has been measured in cetaceans and pinnipeds (Gauthier et al 1998; Lalancette et al 2003). Direct reproductive effects associated with high Hg levels have been documented in bird species in freshwater ecosystems (Burgess and Meyer 2008; Evers et al 2008), and Braune et al (2006) documented egg Hg concentrations in the ivory gull that exceed twice the adverse effect threshold for eggs in the common loon (Evers et al 2003), suggesting that seabirds may be experiencing similar reproductive effects as freshwater birds.…”
Section: Trophic Transfer and Bioaccumulation Of Mehg In Marine Food mentioning
confidence: 99%
“…Specifically, in cetaceans, metal exposure has been correlated with infectious disease mortality, parasitic infections and pneumonias and histopathological changes in lung and kidney tissues [7][8][9]. Cetacean cell culture studies showed that metals can induce cytotoxic, immunotoxic and genotoxic effects [10][11][12][13][14][15][16][17]. Thus, animal and tissue culture studies suggest that metals could be a health concern to cetaceans.…”
Section: Introductionmentioning
confidence: 99%